Advanced treatment of urban wastewater by sand filtration and graphene adsorption for wastewater reuse: Effect on a mixture of pharmaceuticals and toxicity. Issue 1 (March 2015) - Rizzo, L.; Fiorentino, A.; Grassi, M.; Attanasio, D.; Guida, M.
Graphical abstract